Political Cost Incentives for Managing the Property‐Liability Insurer Loss Reserve - GRACE, MARTIN F.; LEVERTY, J. TYLER (Journal of Accounting Research, 2010)
ABSTRACT This paper examines the effect of rate regulation on the management of the property‐liability insurer loss reserve. The political cost hypothesis predicts that managers make accounting choices to reduce wealth transfers resulting from the regulatory process. Managers may under‐state reserves to justify lower rates to regulators. Alternatively, managers may have an incentive to report loss inflating discretionary reserves to reduce the cost of regulatory rate suppression. We find insurers over‐state reserves in the presence of stringent rate regulation. Investigating the impact along the conditional reserve error distribution, we discover that a majority of the response occurs from under‐reserving firms under‐reserving less because of stringent rate regulation.